2020
DOI: 10.1074/jbc.ra120.013553
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of intracellular tau protein from neuronal cells via VAMP8-induced secretion

Abstract: In Alzheimer’s disease (AD), tau — a microtubule-associated protein — becomes hyperphosphorylated, aggregates and accumulates in the somato-dendritic compartment of neurons. In parallel to its intracellular accumulation in AD, tau is also released in the extracellular space, as revealed by its increased presence in cerebrospinal fluid. Consistent with this, recent studies, including ours, have reported that neurons secrete tau, and several therapeutic strategies aim to prevent the intracellular tau accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 83 publications
1
24
0
Order By: Relevance
“…For example, Di Paolo et al (37) revealed APOB as a new link between cholesterol and AD and may underlie AD pathogenesis common to both late-onset AD and early-onset AD. VAMP8 was considered the most core gene in peripheral blood consistent with the results of a previous neuronal models study showing that VAMP8 could increase tau secretion (38). Neuroinflammation mediated by microglia and astrocytes, as well as by peripheral immune cells, has been described as an important contributor to AD (39,40).…”
Section: A B Discussionsupporting
confidence: 79%
“…For example, Di Paolo et al (37) revealed APOB as a new link between cholesterol and AD and may underlie AD pathogenesis common to both late-onset AD and early-onset AD. VAMP8 was considered the most core gene in peripheral blood consistent with the results of a previous neuronal models study showing that VAMP8 could increase tau secretion (38). Neuroinflammation mediated by microglia and astrocytes, as well as by peripheral immune cells, has been described as an important contributor to AD (39,40).…”
Section: A B Discussionsupporting
confidence: 79%
“…Nevertheless, tau protein is also released in the extracellular space and can be found in the CSF. Secretion of tau involves transport from late endosomes to the PM and could help to prevent accumulation of the protein responsible for AD onset [ 70 ]. Vamp8 is an R-SNARE that localizes at late endosomes and that can make complexes together with syntaxin-7, vti1b and syntaxin-8 for homotypic fusion of late endosomes, with syntaxin-17 and SNAP-29 for autophagosome-lysosome fusion or with syntaxin-3 and SNAP-23 for secretion [ 45 , 77 , 78 ].…”
Section: Admentioning
confidence: 99%
“…Interestingly, by overexpressing VAMP8, tau secretion was increased and the amount inside neuroblastoma cells was reduced [ 70 ]. In fact, VAMP8-, Rab7- and Rab9-positive vesicles containing tau were directed to the PM where tau was released.…”
Section: Admentioning
confidence: 99%
See 1 more Smart Citation
“…A related question is: What is unique about the TM domains of STX6 and STX8? The recent finding that overexpression of VAMP8a v-SNARE on late endosomescould also lead to tau secretion from neuronal cells [26] seems to imply that TM domain-mediated tau release might not be limited to syntaxins.…”
Section: Commentarymentioning
confidence: 99%